Datación del "Príncipe" : inicio y culminación - Connell, William J. (Ingenium. Revista Internacional de Pensamiento Moderno y Metodología en Historia de las Ideas, 2014)
This article establishes a new, more precise date for the completion of Machiavelli’s work on The Prince. Newly discovered documents in Florentine Archives from July 1515 reveal that Niccolò Machiavelli and his family were struggling to deal with an unexpected crisis that had befallen them in the previous several months. That crisis must have been none other than the failure of Machiavelli’s Prince to win favor with the book’s dedicatee, Lorenzo de’ Medici the Younger. The presentation of the book to Lorenzo can now be dated between 15 May 1515 and 3 July 1515, and probably toward the beginning of this period. And the final version of the text was completed at some point between 14 February 1515 and the presentation several months later.